SOFT LAW IN INTERNATIONAL INVESTMENT LAW - BINISAROJ (2023)
This paper aims to analyse the concept of soft laws and its significance in international law with special emphasis on its effect on international investment law. Soft laws are legally non-binding but may be construed as politically binding instruments that have legal implications on participants.In this paper, the authors have relied upon the works of legal scholars and arbitral jurisprudence to understand their observations about the role of soft laws such as the United Nations General Assembly (UNGA) Resolution 1803 of 1962 on Permanent Sovereignty over Natural Resources and subsequent related declarations of the Assembly of 1973 and 1974 respectively, the 1968 UNESCO Recommendation concerning the preservation of Cultural Property Endangered by Public or Private Works, the International Covenant on Economic, Social and Cultural Rights (ICESCR), the OECD Guidelines for Multinational Enterprises of 1976, the International Bar Association (IBA) Guidelines on Conflicts of Interest in International Arbitration, and decisions of international courts and tribunals to mention just a few, and apply such observations to the present times to analyse the strengths and drawbacks of soft law in the current international investment law context. The paper argues that although formally non-binding, yet in practice soft law instruments do influence the behavior of states and foreign investors either directly or indirectly. They also play a significant role in the formulation of international law by serving as precursors to the formulation of binding rules by states or by developing the rights and obligations of the parties mainly through interpretation of vague or open-ended investment treaty provisions by arbitral tribunals